Diversity of Diatom Communities in Delaware Tidal Wetland and Their Relationship to Water Quality - Chintapenta, Lathadevi K.; Coyne, Kathryn J.; Pappas, Amanda; Lee, Katherine; Dixon, Connor; Kalavacharla, Venu; Ozbay, Gulnihal (Frontiers in Environmental Science, 2018)
Diatoms are strongly influenced by water quality and serve as indicators of water quality degradation in freshwater systems. Here, sediment and water samples were collected from four sites in Blackbird Creek, DE, a salt marsh characterized as mostly freshwater to low saline brackish (<8ppt). Recent changes in land use resulted in increased agricultural activity, suggesting the need to develop water quality indicators in this region. To test the hypothesis that diatom community composition changes seasonally with variations in water quality parameters, sediment and water samples were collected in 2009 and 2010 for analysis. Water temperature, salinity, pH, and dissolved oxygen were measured as well as water and sediment dissolved nutrient concentrations (nitrate, ammonia, and total and reactive phosphorous). DNA was extracted from sediments and changes in diatom community composition were evaluated by amplification of 18S rRNA gene using diatom-specific primers, followed by Terminal Restriction Fragment Length Polymorphism (TRFLP) analysis. Shannon (H') index for TRFLP profiles ranged from 2.5 to 3.0 and Simpson (Ds) index was 0.9 which infers moderate levels of diatom species richness and high diversity in these study sites. Although there were no water quality parameters that were significantly correlated with diatom community composition as determined by TRFLP patterns, temperature was the most highly correlated (r=0.203). Dissolved oxygen, salinity, and pH of water also had moderate but insignificant impacts on the diatom community. Further analysis of cloned 18S rRNA sequences revealed the presence of diatom taxa that tolerate wide salinity ranges, and included Navicula, Cyclotella, Thalassiosira and Skeletonema. Entomoneis sp. were also present in the spring and fall seasons. Overall, results in this study demonstrate significant differences in water qualities among the study years but little change in diatom community composition between study sites and seasons, but may serve as a baseline for future studies.